E-book user behaviour in academic libraries: The role of user agents in perception and satisfaction - Pervaiz, Ahmad; Mark, Brogan; Ahmad, Pervaiz; Brogan, Mark (Malaysian Journal of Library and Information Science, 2016)
Based on technology adoption theories and allied frameworks, this paper aims to explore e-book user behaviour around multiple dimensions of the role of user agents in formation of patterns, attitudes, perception and satisfaction with electronic resources in an academic and research library context. A convenience sample of academics, staff, and students at Edith Cowan University (ECU) voluntarily self-reported their e-book information behaviour via online survey. In terms of agent/platform satisfaction, desktop computer and laptop/netbook had the most satisfied users. Significant factors in e-resource use and agents/platforms were found to include familiarity (collection awareness and differentiation between resource types), usability (discovery, information retrieval and readability, and library interface ease of use), utility (collection sufficiency), hedonic attributes (attractiveness), culture of use and habituation. Users satisfied with laptops/netbooks as user agents also expressed overall satisfaction with library e-books. E-book users’ information behaviour was found to be consistent with major technology adoption theories and frameworks in terms of e-resources and their use platforms.